Improving children's patient experience with a mobile hospital clowning application - Initial user experiences from the clowns' perspective - Eira Erola; Johanna Viitanen; Nina Karisalmi; Kaisa Savolainen (Finnish Social and Health Informatics Association, 2023)
eHealth solutions are increasingly being developed to support patient care and improve patients' experiences (PXs). Recently, the coronavirus disease 2019 (COVID-19) pandemic and the shortage of nurses in several countries, including Finland, have further underscored the need for new digital services. In the context of children's hospitals, care-supporting services include hospital clowns who work to provide emotional support for children and improve their PXs. Hospital clowns are known to have a positive impact on children's PX. The Finnish hospital clown organization Sairaalaklovnit ry has published its first mobile application Sairaalaklovnit to provide a digital contact platform to reach patients remotely via messages. The application is mainly targeted at child patients and includes both entertainment and messaging facets for communication between child patients and hospital clowns. The two main user groups for this application can be considered to be child patients and hospital clowns. This article presents the data and results found during a study related to the user experience (UX) of the Sairaalaklovnit application. With the research questions, "Which aspects influence the UX of the hospital clown application?" and more specifically, out of the two user groups, "How do Finnish hospital clowns experience the new hospital clown mobile application?", this study aims to gain an understanding of how Finnish hospital clowns experience the newly developed application for expanding physical contact with patients into a digital form. The qualitative data used in this article were collected in the summer of 2022 through an online questionnaire (n = 5) and semi-structured interviews (n = 3) with hospital clowns. The hospital clowns were mostly satisfied with the published application, but some deficiencies were mentioned. Most of the complaints were related to technical issues. However, the application was seen as a useful tool that can bridge physical and digital contact with children. The developer has been made aware of the technical issues and fixes expected in the future. For future research, it can be beneficial to rerun the UX study for the hospital clowns and possibly with a larger sample to see whether there have been any changes after the technical issues have been solved. Moreover, studying how child patients, which constitute the other user group, experience the new application, can prove to be beneficial for possible future development.